Review of the most common chemometric techniques in illicit drug profiling. (September 2019) - Popovic, Ana; Morelato, Marie; Roux, Claude; Beavis, Alison
Graphical abstract: Highlights: The most common chemometric techniques in drug profiling are presented in this review. Applications of comparison metrics, pattern recognition & class prediction are explored. The outcomes from these techniques can be used to support intelligence-led policing. Abstract: The information generated through drug profiling can be used to infer a common source between one or several seizures as well as drug trafficking routes to provide insights into drug markets. Although well established, it is time-consuming and ineffective to compare all drug profiles manually. In recent years, there has been a push to automate processes to enable a more efficient comparison of illicit drug specimens. Various chemometric methods have been employed to compare and interpret forensic case data promptly. The intelligence that is produced can be used by decision-makers to disrupt or reduce the impact of illicit drug markets. This review highlights the most common chemometric techniques used in drug profiling and more specifically, the most efficient comparison metrics and pattern recognition techniques outlined in the literature.